Perioperative Respiratory Adverse Events Among Pediatric Surgical Patients in University Hospitals in Northwest Ethiopia; A Prospective Observational Study - Wudineh, Desalegn Muche; Berhe, Yophtahe Woldegerima; Chekol, Wubie Birlie; Adane, Habtu; Workie, Misganaw Mengie (Frontiers in Pediatrics, 2022)
Introduction: Perioperative respiratory adverse events (PRAEs) are frequent among pediatrics surgical patients and are accountable for 3/4th of perioperative critical incidents and 1/3rd of cardiac arrests. Objective: Assess the prevalence and factors associated with PRAEs among pediatric surgical patients in University Hospitals in Northwest Ethiopia, 2020. Methodology: Ethical approval obtained and prospective observational study was conducted among 210 pediatric surgical patients. Perioperative respiratory adverse events were defined as the occurrence of any episode of single/combination of coughing, breath holding, hypoxemia, laryngospasm and bronchospasm. Bivariate and multivariate binary logistic regression analyses were performed and variables with p-value < 0.05 at 95% confidence interval were considered as statistically significant. Results: The prevalence of PRAEs was 26.2% (CI: 20.5 – 30.9%). A total of 129 episodes of PRAEs were occurred and of them, 89 (69.0%) were occurred in the postoperative period. Desaturation was the predominant adverse event which was observed 61 (47.3%) times. Age < 1 year (AOR: 3.6, CI: 1.3 – 10.0), ASA ≥ 3 (AOR: 5.2, CI: 1.9 – 22.9), upper respiratory tract infections (URTIs) (AOR: 7.6, CI: 1.9 – 30.2), secretions in the upper airway (AOR: 4.8, CI: 1.4 – 15.9) and airway related surgery (AOR: 6.0, CI: 1.5 – 24.1) were significantly associated with PRAEs. Conclusions: Prevalence of PRAEs was high among pediatric surgical patients; the postoperative period was the most critical time for the occurrence of PRAEs and desaturation was the commonest PRAE. Age < 1 year, URTIs (recent or active), secretions in the upper airways, ASA ≥ 3 and airway related surgery were significantly associated with PRAEs. Clinicians should perform effective risk assessment, preoperative optimization and preparation for the management of PRAEs.